2017
DOI: 10.1017/s0954579417001298
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stress-related epigenetic regulation of the glucocorticoid receptor gene promoter during early development: The role of child maltreatment

Abstract: Epigenetics processes may play a vital role in the biological embedding of early environmental adversity and the development of psychopathology. Accumulating evidence suggests that maltreatment is linked to methylation of the glucocorticoid receptor gene, nuclear receptor subfamily 3, group C, member 1 (NR3C1), which is a key regulator of the hypothalamic–pituitary–adrenal axis. However, prior work has been exclusively cross-sectional, greatly constraining our understanding of stress-related epigenetic process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 75 publications
7
40
1
Order By: Relevance
“…Longitudinal studies are a common tool in human developmental studies and could be exploited here to identify both when differences emerge as well as when (and how) they are or can be ameliorated. Indeed, only one paper in this review measured change in DNA methylation (Parent et al, ; saliva sample), and the results are opposite to the interpretation usually made from similar single time point data (decreasing and lower time 2 methylation for the maltreated children vs. non‐maltreated children at NR3C1 exons 1 D and 1 F ). The human studies also nearly entirely lack attempts at intervention, pharmacologically, as is done in animal models, but also behaviorally—despite the literally hundreds of commentaries and reviews that include reference to this possibility (e.g., Heim & Binder, ; Szyf & Bick, , Turecki & Meaney, ).…”
Section: Discussioncontrasting
confidence: 68%
“…Longitudinal studies are a common tool in human developmental studies and could be exploited here to identify both when differences emerge as well as when (and how) they are or can be ameliorated. Indeed, only one paper in this review measured change in DNA methylation (Parent et al, ; saliva sample), and the results are opposite to the interpretation usually made from similar single time point data (decreasing and lower time 2 methylation for the maltreated children vs. non‐maltreated children at NR3C1 exons 1 D and 1 F ). The human studies also nearly entirely lack attempts at intervention, pharmacologically, as is done in animal models, but also behaviorally—despite the literally hundreds of commentaries and reviews that include reference to this possibility (e.g., Heim & Binder, ; Szyf & Bick, , Turecki & Meaney, ).…”
Section: Discussioncontrasting
confidence: 68%
“…In the first series of studies that we know of to assess DNA methylation at more than one time point, Parent and colleagues found that maltreated preschoolers exhibited significantly lower levels of DNA methylation of NR3c1 6 months after state agency involvement (Parent et al, 2017). In this same sample, Parade and colleagues found that maltreated children who received more services exhibited increases in FKBP5 methylation in one particular region, which may be related to better regulation of the neuroendocrine stress response system.…”
Section: Fetal Programming Models: a Need For Testable Hypotheses Thamentioning
confidence: 99%
“…However, the epigenetic effect of service utilization was not measured in the children with maltreatment; thus, more studies are needed to conclude the service utilization or other interventions can induce reversal of maltreatment-related epigenetic effects. Child maltreatment is associated with higher initial levels of NR3C1 promoter methylation within six months of documented maltreatment but lower methylation of NR3C1 one year after the maltreatment exposure [105]. This dynamic stress-related DNA methylation changes of NR3C1 reflects the organisms’ early acute response resulting in neurobehavioral dysregulation and later adaptive changes for maintaining high levels of readiness for chronically repeated stressful or unstable conditions [105,106].…”
Section: Epigenetic Adaptation: Negative Effectsmentioning
confidence: 99%
“…Child maltreatment is associated with higher initial levels of NR3C1 promoter methylation within six months of documented maltreatment but lower methylation of NR3C1 one year after the maltreatment exposure [105]. This dynamic stress-related DNA methylation changes of NR3C1 reflects the organisms’ early acute response resulting in neurobehavioral dysregulation and later adaptive changes for maintaining high levels of readiness for chronically repeated stressful or unstable conditions [105,106]. Overall, these studies demonstrate the potential reversibility of epigenetic processes, although further work is needed to better characterize and demonstrate such phenomenon.…”
Section: Epigenetic Adaptation: Negative Effectsmentioning
confidence: 99%